Evaluation of particle swarm optimization for strength determination of tropical wood polymer composite - Marina Yusoff; Alya Nurizzati Mohd Basir; Norhidayah A Kadir; Shahril Anuar Bahari (Institute of Advanced Engineering and Science, 2020)
A wood-polymer composite (WPCs) refers to wood-based components that are coupled with polymers to produce a composite material. Obtaining the best strength for the tropical WPCs is still a lack of research mainly for the tropical timber species and require a large consumption of time and cost. This paper highlighted the evaluation of particle swarm optimization (PSO) to assist in finding the optimal value of the composition of tropical WPCs to obtain the best strength that would offer a betterment in a quality product of WPCs. The findings demonstrate that PSO has been shown as a viable and efficient method for WPCs strength. The composition of Sentang, wood sawdust of 50%, HDPE of 49% and 1% coupling agent is demonstrated the best strength for the WPC. The employment of PSO as an assisted tool would give significant benefit to the manufacturer and researcher to determine the composition of material with less cost and time.